Mathematical Models of Blast-Induced TBI: Current Status, Challenges, and Prospects - Gupta, Raj K.; Przekwas, Andrzej (Frontiers in Neurology, 2013)
Blast induced traumatic brain injury (TBI) has become a signature wound of recent military activities and is the leading cause of death and long-term disability among U.S. soldiers. The current limited understanding of brain injury mechanisms impedes the development of protection, diagnostic and treatment strategies. We believe mathematical models of blast wave brain injury biomechanics and neurobiology, complemented with in vitro and in vivo experimental studies, will enable a better understanding of injury mechanisms and accelerate the development of both protective and treatment strategies. The goal of this paper is to review the current state of the art in mathematical and computational modeling of blast induced TBI, identify research gaps and recommend future developments. A brief overview of blast wave physics, injury biomechanics and the neurobiology of brain injury is used as a foundation for a more detailed discussion of multiscale mathematical models of primary biomechanics and secondary injury and repair mechanisms. The paper also presents a discussion of model development strategies, experimental approaches to generate benchmark data for model validation and potential applications of the model for prevention and protection against blast wave TBI.